2017
DOI: 10.1097/phh.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Facilitators and Barriers to Local Health Department Workers' Participation in Infectious Disease Emergency Responses

Abstract: Context Local health departments play a key role in emergency preparedness and respond to a wide range of threats including infectious diseases such as seasonal influenza, tuberculosis, H1N1, Ebola, and Zika. To successfully respond to an infectious disease outbreak, local health departments depend upon the participation of their workforce yet studies indicate that sizable numbers of workers would not participate in such a response. The reasons why local health department workers participate, or fail to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Of the 40 studies identified, 33 (n = 33; 82.5%) identified specific barriers to willingness (Table 2). 2,4,[8][9][10][11][13][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The barriers to willingness could be categorized into the following four groups: concern and perceived risk, interpersonal factors, job-level factors, and outbreak characteristics.…”
Section: Barriers To Willingnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 40 studies identified, 33 (n = 33; 82.5%) identified specific barriers to willingness (Table 2). 2,4,[8][9][10][11][13][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The barriers to willingness could be categorized into the following four groups: concern and perceived risk, interpersonal factors, job-level factors, and outbreak characteristics.…”
Section: Barriers To Willingnessmentioning
confidence: 99%
“…2,14 Worker Support Systems-Six (n = 6; 15.0%) studies identified worker support systems to help facilitate willingness. 2,14,16,28,35,39 Valued supports included telephone and email access, 2 transportation support, 2,14,39 provision of food 2 and accommodation, 2,14 and guaranteed financial supports, such as life and/or disability insurance or hazard pay. 14,39 A study of WTR among nursing students further supported the value of providing food, opportunities for rest and personal hygiene (eg, showers), and organizational programs to support mental and spiritual health, such as available chaplains.…”
Section: Facilitators Of Willingnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that male gender, being a physician, having a full-time job, self-protection, and communication equipment for staff, and basic needs such as water have a positive impact on the willingness to work in such events (55,60,61). Motivation facilitators for working in infectious emergencies include access to vaccination and personal protective equipment, flexible work shift, taking care of staff children, and information sharing (57).…”
Section: Resourcesmentioning
confidence: 99%
“…During the 2014–2016 West Africa EVD outbreak, the provision of supportive care varied across ETUs and over time. While previous reports identified factors that motivated or hindered the mobilization of health professionals [ 6 , 7 ], there were no clinical practice guidelines on a core set of supportive care measures that should be guaranteed to all patients treated in ETUs.…”
Section: Introductionmentioning
confidence: 99%